A complete guide to quality in small-scale wine making - Considine, John Anthony (Academic Press, Elsevier, 2014)
"As the wine industry has experienced a period of rapid global expansion, there is a renewed emphasis on quality and consistency even within the small winery industry. Written for the small production program, A Complete Guide to Quality in Small-Scale Wine Making is for the novice to intermediate level winemaker."